ASPECTOS SOROEPIDEMIOLÓGICOS E MOLECULARES DAS HEPATITES A e E EM DIFERENTES GRUPOS POPULACIONAIS NOS ESTADOS DE SÃO PAULO E MATO GROSSO DO SUL - Sabrina Moreira dos Santos Weis (2022)
The aim of this study was to characterize the seroepidemiological and molecular aspects of infections caused by hepatitis A (HAV) and E (HEV) viruses in different population groups in Mato Grosso do Sul (MS) and São Paulo (SP). In MS, the population groups studied were: blood donors (BD), Afro-descendant communities (AFD), Japanese immigrants and their descendants (JMS), waste collectors (PC), incarcerated persons (PPL), incarcerated persons with active tuberculosis (PTB), men who have sex with men (HSHMS), transgender women (TW), patients with chronic hepatitis C (PHCV) and people living with HIV/AIDS (PVHA). In SP, the present study was conducted in the population of Japanese immigrants and their descendants (JSP). In addition, we aimed to estimate the seroreversion and incidence rates of HEV infection among incarcerated persons. A total of 3243 samples were tested for serological markers of HAV infection (total anti-HAV and/or IgM) using an immunochemiluminescent assay (VITROS Eci), and a total of 5301 samples were tested for detection of HAV exposure markers. HEV (anti-HEV IgG and IgM) using enzyme immunoassay (WANTAI HEV ELISA kit). After extraction, viral RNA from anti-HEV IgM samples was amplified by RT-qPCR. The prevalence of the anti-HAV markers found was 78.6% (95% CI: 77.1 – 79.9). The highest prevalence was observed in the PC population (96.4%), followed by PVHA (95.0%), PHCV (93.8%), PTB (85.2%), JMS (78.9%), JSP (69.5%) and AFD (66.9%). The factors associated with the presence of total anti-HAV in MS population groups were: age over 30 years (AFD and JMS), having low educational level (PC, PTB), having a steady sexual partner (JMS), being female, and having been recruited from the dump (PC), and irregular condom use (AFD). In São Paulo (JSP population), the factors associated with this infection were: age over 30 years, not being born in São Paulo, being an immigrant or being Japanese child, not being an Okinawan descent, and not having a tattoo. Of the 1010 samples tested for the anti-HAV-IgM marker, only one sample was positive. The prevalence of HEV exposure found in this study was 9.8% (95% CI: 9.0 – 10.7). Only 50 participants were positive for anti-HEV IgM (1.1%), of which only 1 had detectable HEV RNA and belonged to the AFD population. The highest prevalence of HEV infection was found in the PC population (14.8%), followed by PPL (14.6%), PTB (12.9%), PVHA (9.4%), JSP (8.9 %), HSHMS (8.2%), TW (8.1%), PHCV (7.4%), AFD (6.7%), BD (6.4%) and JMS (6.0%). The factors associated with HEV exposure in the populations studied were: age over 30 years (PTB, JSP), not having been born in MS (BD and PC), low educational level (PPL, HSHMS), regular condom use (PTB) and heroin use (PPL). The incidence rate of HEV infection in incarcerated persons was 1.0/100 person-year, and the seroreversion rate was 7.8/100 person-year. This study indicates a high prevalence of anti-HAV markers in most of the studied populations, despite the existence of young individuals susceptible to this infection in the JMS, JSP, and AFD populations. Therefore, the development of adequate and accessible strategies for vaccination against hepatitis A is recommended in these population groups. Epidemiological data on HEV infection in the studied population groups demonstrate that the prevalence may vary according to the studied population and the occurrence of new cases (seroconversion) was found, as well as seroreversion of HEV infection markers in prison environments. In addition, the data generated from this research can contribute to a better understanding of these infections in Brazil, highlighting the importance of more specific public health interventions for different group populations.